Action Research on Perceptions, Experiences and Expectations on Alternative Assessments in the Sri Lankan University Context (International Journal of Multidisciplinary Research and Explorer, 2023)
This action research investigates perceptions, experiences, and expectations regarding alternative assessments among second-year students specializing in Human Resource Management within the Faculty of Commerce and Management Studies at a Sri Lankan university. Amid the challenges posed by the pandemic, the study, implemented for an Advanced English for Commerce and Management Studies course, replaced the conventional final exam with three alternative assessment methods. Conducted with 110 participants, the research employed a mixed-methods approach, distributing questionnaires to all students and conducting interviews with a randomly selected subset of 15 participants. The participants had studied English for one year, and their language proficiency was assessed at CEFR level B2 based on a test taken after their first year. The findings reveal a preference among students for alternative assessments over traditional tests, citing the reduced stress associated with non-traditional evaluation methods. This preference persisted even in the context of the pandemic, underscoring the potential of alternative assessments as a viable option for future implementations. The results of this study hold significance for educational authorities, providing valuable insights to inform decision-making processes regarding assessment methods, especially in times of crisis and beyond.